Inconsistencies of the Disease Activity Assessment Tools for Psoriatic Arthritis: Challenges to Rheumatologists - GEZER, HALİSE HANDE; DURUÖZ, MEHMET TUNCAY (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2022)
Objective: Currently, concerning the evaluation of psoriatic arthritis (PsA), there is no agreement on a standardized composite index for disease activity that includes all relevant domains. The present study sought to assess the rates of remission (REM)/low disease activity (LDA) and disease states [minimal disease activity (MDA), very low disease activity (VLDA)] as defined by diverse activity scales (DAPSA, DAS28-ESR) in an attempt to display discrepancies across these assessment tools for peripheral PsA. Methods: The study involved 758 patients (496 females, 262 males; mean age 47,1 years) with peripheral PsA who were registered to the Turkish League Against Rheumatism (TLAR) Network. The patients were assessed using the DAS28-ESR, DAPSA, MDA, and VLDA. The overall yield of each scale was assessed in identifying REM and LDA. The presence or absence of swollen joints was separately analysed. Results: The median disease duration was 4 years (range 0-44 years). According to DAPSA and DAS28-ESR, REM was achieved in 6.9% and 19.5% of the patients, respectively. The rates of MDA and VLDA were 16% and 2.9%, respectively. Despite the absence of swollen joints, a significant portion of patients were not considered to be in REM (296 (39.1%) patients with DAS28-ESR, 364 (48%) with DAPSA, and 394 (52%) with VLDA). Conclusion: Patients with peripheral PsA may be assigned to diverse disease activity levels when assessed with the DAS28-ESR, DAPSA, MDA and VLDA, which would inevitably have clinical implications. In patients with PsA a holistic approach seems to be necessary which includes other domains apart from joint involvement, such as skin involvement, enthesitis, spinal involvement, and patient-reported outcomes. (C) 2021 Societe franc , aise de rhumatologie. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Remission; Disease activity; Psoriatic arthritis; Composite index; ACTIVITY STATES; CLASSIFICATION CRITERIA; ACTIVITY INDEXES; REMISSION; RECOMMENDATIONS; INSTRUMENT; MANAGEMENT; TARGET